'Dayes of Gall and Wormwood': public religious disputation in England, 1558-1626 - Rodda, Joshua (2012)
This study examines a form of religious debate that saw Catholic priests and ministers across the reformed spectrum arguing in direct opposition to one another, and drawing on long-standing academic forms and intellectual ideals in doing so. Public religious disputation is first defined and placed in its religious, cultural and intellectual context, alongside formal disputation in the universities, printed controversy, literary dialogue and other manifestations of discourse and debate. The structures, tropes and tactics of the formal, academic process – as used in public or ‘professional’ controversial debate – are then detailed, in order to give a more precise definition, and a framework for the analysis of individual events.